2018
DOI: 10.3390/v10050236
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the Interaction Energies between Amino Acid Residues of the Measles Virus Hemagglutinin and Its Receptors

Abstract: Measles virus (MV) causes an acute and highly devastating contagious disease in humans. Employing the crystal structures of three human receptors, signaling lymphocyte-activation molecule (SLAM), CD46, and Nectin-4, in complex with the measles virus hemagglutinin (MVH), we elucidated computationally the details of binding energies between the amino acid residues of MVH and those of the receptors with an ab initio fragment molecular orbital (FMO) method. The calculated inter-fragment interaction energies (IFIEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 40 publications
3
39
1
Order By: Relevance
“…The second term in this equation corresponds to pair interaction energy (PIE) [9] or inter-fragment interaction energy (IFIE) [10,23], which is quite useful for interaction analyses [8,10] (See Refs [11][12][13][14][15][16][17] when necessary). We therefore used IFIE for the interaction analysis in this paper.…”
Section: Fmo Calculationsmentioning
confidence: 99%
“…The second term in this equation corresponds to pair interaction energy (PIE) [9] or inter-fragment interaction energy (IFIE) [10,23], which is quite useful for interaction analyses [8,10] (See Refs [11][12][13][14][15][16][17] when necessary). We therefore used IFIE for the interaction analysis in this paper.…”
Section: Fmo Calculationsmentioning
confidence: 99%
“…The suggestion that the mutated amino acids (I61P, H62A, I210P A211R, S226A and R227A) in mSLAM1 have a crucial role in PPRV H binding to SLAM is in agreement with previous findings [ 14, 29–31 ]. Computational analysis showed that K77 and E123 in human and canine SLAM play pivotal roles in binding to the H protein of MV and CDV [ 16, 42, 43 ]. The two residues are known to be well conserved among the reported mammalian SLAMs.…”
Section: Discussionmentioning
confidence: 99%
“…The FMO method is already recognized as a useful drug design tool to analyze ligand binding interactions, incorporating electrostatic interactions such as hydrogen bonds and dispersion forces such as CH/π interactions, using the pair interaction energy decomposition analysis (PIEDA) [4,5] and fine fragmentation by the functional group unit, rather than the amino acid residue unit and the whole ligand [6][7][8]. Recently, the IFIE analysis and its energy decomposition analysis have been applied to the prediction of binding affinity for rational drug design [9][10][11][12][13][14][15][16][17][18]. Using FMO calculations of tens of complexes for one target protein, the essential and characteristic interactions of the ligand binding mode can be abstracted from the IFIE and PIEDA data by clustering methods [19][20] and singular value decomposition [21].…”
Section: Introductionmentioning
confidence: 99%